Justice and Employee Engagement a Case of Nile Breweries Uganda - Rebecca Ajolo (Uganda Christian University, 2026)
The study was carried out to investigate the relationship between organizational justice and employee engagement in Nile Breweries Uganda. The specific objectives of the study were to examine the level of employee engagement, examine the perception of employees on organizational justice, and finally determine the relationship between employee engagement and organizational justice. A descriptive correlational study was used to answer the study objectives, which was based on the quantitative study design. The study was carried out among 172 employees of Nile Breweries Uganda, who responded to structured questionnaires on employee engagement and perception of organizational justice. The data was analyzed using SPSS Version 26 software. Basically, the employees are super committed and engaged, scoring high marks in the study. In addition, the study found that employees perceived organizational justice to be high, with a mean of 3.85. Moreover, interactional justice was the highest, which showed that communication was essential in enhancing employee engagement. The study concluded that organizational justice was essential in enhancing employee engagement, which was further confirmed by the strong positive relationship between employee engagement and organizational justice, which was significant at 0.01, with a Pearson’s r of 0.635. In addition, regression analysis showed that interactional justice was the strongest predictor of employee engagement, with a regression coefficient of 0.311. Key Words: Organizational Justice, Employee Engagement, Fairness, Nile Breweries Uganda.
Undergraduate